The Distribution of Returns to Education for People with Disabilities - Daniel J. Henderson; Andrew Houtenville; Le Wang (Institute of Labor Economics (IZA), 2017)
This note takes a first look at the distribution of returns to education for people with disabilities, a particularly disadvantaged group whose labor market performances have not been well studied or documented. Using a nonparametric approach, we uncover significant heterogeneity in the returns to education for these workers, which is drastically masked by the conventional parametric methods. Based on these estimates, we construct the Sharpe ratio of human capital investment (taking into account its substantial risk), and our results corroborate on the claimed importance of human capital in improving these workers' wages. Our stochastic dominance tests, however, show that the returns to education for workers with disabilities, as a group, may have been affected more adversely in the most recent recession, relative to their non-disabled counterparts.
Keywords: C14; I12; I26; I31; 330; disability; education; risk; heterogeneity